Evaluating the impact of check dam construction on runoff processes in Al-Dayer watershed using a physically-based hydrologic model - Ahmed M. Al-Areeq; Isam H. Aljundi (Geomatics, Natural Hazards & Risk)
The widespread use of check dams for water resource management and environmental conservation purposes has been well-established for centuries. Nevertheless, to further improve our understanding of their effectiveness, this study provides a novel evaluation of how check dam construction has impacted the hydrologic processes in the Al-Dayer watershed. A state-of-the-art, fully distributed, physically based hydrologic model (GSSHA) was used to simulate the impact of check dams on runoff duration, runoff volume, and peak discharge using hydrographs under different check dam scenarios, which include different check dam locations and different numbers of check dams. The study results reveal that constructing check dam significantly reduces peak discharge and runoff volume while increasing runoff duration. Furthermore, compared to longer return periods, the runoff coefficient decreases significantly for shorter. The three check dams reduced the runoff volume, peak discharge, and runoff coefficient by 3.6%, 36.53%, and 6.9% for 2 years return period and 2.14%, 37.9%, and 4.2% for 100 years, while the entire system (five check dams) reduced them by 3.68%, 39.16%, and 7.1% for 2 years and 1.83%, 37.9%, and 3.59% for 100 years. The results highlight the importance of considering the number and location of check dams for optimal impact on runoff processes within a watershed.